The domestication of media, the mediatization of homes material culture of media technologies and changes to domestic spaces in Iran - A. Habibi; S.A. Yazdanfar; M. Hamzenejad; A. Varij Kazemi (Taḥqīqāt-i Farhangī-i Īrān)
Today's house is very different from a traditional or pre-industrial one. Numerous factors have been involved in home changes, but none of them has affected the home and domestic space as much as with the emergence of modern technologies. The purpose of this study is to investigate the process of linking and companionship of Iranian homes and media outlets and their mutual effects. Regardless of the content of the media, which is often considered, focusing on the material culture of media outlets, especially television, the paper pays attention to the process of domestication of media technologies and the mediatization of the home in Iran. The findings show that media outlets faced internal and external resistance when entering Iranian homes and in its process of domestication. The common denominator of resistance, despite their different origins, is being ideological. The findings also show that a process of the mediatization of homes in Iran is recognizable, which began with the arrival of radio and, consequently, electricity in Iranian homes. A process that is gradually moving towards increasing home smarting. By moving in this direction, the house itself becomes a medium, the one that is moving towards a "connected home" by connecting it with other homes, neighborhoods and smart cities.